2020
DOI: 10.1101/2020.07.22.216416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal dynamics between interictal epileptiform discharges and ripples during associative memory processing

Abstract: We describe the spatiotemporal course of cortical high-gamma activity (HGA), hippocampal ripple activity and interictal epileptiform discharges (IEDs) during an associative memory task in 15 epilepsy patients undergoing invasive electroencephalography (iEEG). Successful encoding trials were significantly greater HGA in hippocampus and frontal regions. Successful recall trials manifested sustained HGA in occipital pole and hippocampus compared to failed responses. Hippocampal ripple rates were greater during su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Specifically, our findings highlight the early development of cognitive specificity in ripple activation, which shows notable selectivity towards explicit memory judgments in young children. This reinforces the notion that awake hippocampal ripples are closely tied to mnemonic processes that are consciously accessible and reportable (Henin et al, 2021;Kunz et al, 2022;Norman et al, 2019Norman et al, , 2021Vaz et al, 2019), as opposed to the more automatic, sensory-driven components, that contribute to the sense of familiarity in a more implicit manner (Eichenbaum et al, 2007). parents before surgery.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Specifically, our findings highlight the early development of cognitive specificity in ripple activation, which shows notable selectivity towards explicit memory judgments in young children. This reinforces the notion that awake hippocampal ripples are closely tied to mnemonic processes that are consciously accessible and reportable (Henin et al, 2021;Kunz et al, 2022;Norman et al, 2019Norman et al, , 2021Vaz et al, 2019), as opposed to the more automatic, sensory-driven components, that contribute to the sense of familiarity in a more implicit manner (Eichenbaum et al, 2007). parents before surgery.…”
Section: Discussionsupporting
confidence: 79%
“…They have been extensively linked to declarative memory retrieval in humans (Dickey et al, 2022;Henin et al, 2021;Khuvis et al, 2021;Kunz et al, 2022;Norman et al, 2019Norman et al, , 2021Sakon and Kahana, 2022), and have been shown to support memory-guided decision making (Fernández-Ruiz et al, 2019;Jadhav et al, 2012;Shin et al, 2019) and offline memory consolidation (Maingret et al, 2016;Rothschild et al, 2017;van de Ven et al, 2016) in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 However, our results are in contrast with other studies that have reported no effect of IS in the MTL on memory encoding, 5,21,22 although one recent study also reported impairment. 13 Likely, our methods account for the discrepancy between those studies and ours. The verbal free task used here may be more in detecting a TCI/TMI during the encoding period than other tasks.…”
Section: Is In the Left Hippocampus Disrupt Verbal Episodic Memory En...mentioning
confidence: 70%
“…7,8 Furthermore, this is in accordance with a recent study that found a selective temporal impairment during stimulus presentation using an associative memory task. 13 However, another study reported that IS occurring before or during the presentation of a cognitive stimulus decrease memory performance. 40 More research that takes into consideration IS timing and performance might provide further insights.…”
Section: Is In the Left Hippocampus Disrupt Verbal Episodic Memory En...mentioning
confidence: 99%
See 1 more Smart Citation